Weight bias among health care providers for children in UAE - M. Abdel Reheim, Naguib; Gomaa Ramadan Ali, Nehad; Khot, Shaf; Vamegh, Motahareh; Anwar, Mohammad; Swilem, Mamdouh (International Journal of Research in Medical Sciences, 2017)
Background: This research looks at weight bias among healthcare providers for children in UAE. Methods: This study was done through self-administered questionnaire. Our targets were health care providers for children working in both governmental and private hospitals in UAE. 198 participants were enrolled in the study after exclusion of invalid questionnaires. Results: While 15.4% of healthcare professions in our study acknowledged practice of weight bias during care of obese children, 52.5% denied and 32.1% are not sure about it. 149 participants (76%) believed that failure of obesity management in children is attributed to their weak willpower and poor commitment. Compared with normal children, overweight/obese children are considered less complaint by 59% of our participants, less active by 78.2%, less willpower by 59.5%, less confident by 73.2% and less intelligent by 17.7%. Finally, 10% of our participants consider treatment of overweight/obesity is a waste of time. Conclusions: This study shows significant weight bias among healthcare profession which can occur unintentionally. Weight bias among health care providers affects the quality of medical care of obese children. Education, training and increasing awareness of weight bias among health care providers in UAE is an initial and essential step to decrease the risk of weight bias which is a significant barrier in management of childhood obesity.